The survivors of gastroschisis. Issue 2 (1st August 1997) - Davies, Brian W; Stringer, Mark D
Abstract : AIMS: To assess the long term morbidity and quality of life in survivors of gastroschisis. DESIGN: All babies born with gastroschisis between 1972 and 1984 and who survived more than one year were identified. Those who could be traced were questioned about their general health, growth, abdominal symptoms, cosmetic concerns, education, employment, and fertility. RESULTS: Of the 35 patients, two have died, seven could not be traced, and three declined to be interviewed. Twenty three subjects (70% of survivors) with a median age of 16 years (range 12–23 years) responded. Twenty two (96%) were in good health and overall growth was within normal limits. Eight subjects (35%) have had further surgery related to gastroschisis, including two for adhesive small bowel obstruction and three for scar complications. In 13 (57%), absence of an umbilicus caused distress during childhood. CONCLUSION: Most gastroschisis survivors can eventually expect normal growth and good health. Adhesive bowel obstruction is an uncommon, but potentially late, complication. The umbilicus should be conserved during gastroschisis repair.